EFEKTIVITAS PENERIMAAN PAJAK DAERAH DI WILAYAH BANJAR BAKULA TAHUN 2020 - 2022 - Radhita Inayah; Juniar, Asrid; Abidin, M. Zainal (Universitas Lambung Mangkurat, 2022)
This research aims to determine the effectiveness of regional tax revenues in the Banjar Bakula area in 2020 - 2022. Regional tax revenues have a great influence on local original income (PAD). The research location was carried out by the Regional Revenue Agency Office of South Kalimantan Province, Palam, Cempaka sub-district, Banjarbaru city, South Kalimantan, as the agency that manages regional taxes throughout the province of South Kalimantan. The data collection technique used by researchers is documentation, namely a data collection technique that is not directly aimed at research subjects, but rather at certain documents, in the form of notes, transcripts, books, agendas, newspapers and so on. From the research results, regional taxes in the Banjar Bakula area can be classified as effective because they can realize regional tax targets in the years studied by researchers, but there are also several regions that have not been able to realize regional taxes in those years, they have not been realized because of the collection targets. Regional taxes are quite large so they can cause regional realization to rise and fall.